Development Of Mobile Multimedia Module With An Ecological Awareness Based On Daily Project Learning - Wahyuni, Holy Ichda; Hendarwati, Endah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Education and schools have great potential to support the success of efforts to instill the value of ecological awareness amidst the problems of environmental damage. The development of mobile multimedia modules designed with the concept of a daily project-based learning approach makes ecological education more meaningful and contextual. The purpose found out the method of implementing the value of ecological awareness through the development of mobile multimedia modules for elementary school students using a daily project-based learning approach. This type of research was research and development (research and development). The development model for this multimedia module is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model from Lee & Owens. The results of the material validation showed that the overall average value of the validation is 3.6 in a very valid category. Media validation with an average value of 3.4 categories was valid. User response showed that an average number of 3.2 indicating a positive response. The test results on students showed the value of Sig. (2 tailed) was 0.000 < 0.05. Therefore, it can be concluded that there was a difference in the average Pre-Test and Post Test, which meant there was a change that showed the effectiveness of implementing ecological awareness values through the development of mobile multimedia modules for elementary school students with a daily project-based learning approach. The results of students’ daily activities in the project also showed good and very good categories.